Confirmation of the presence of zoonotic Trichobilharzia franki following a human cercarial dermatitis outbreak in recreational water in Slovakia - Gulyás, Kristián; Soldánová, Miroslava; Orosová, Martina; Oros, Mikuláš (Parasitology research, 2020)
Human cercarial dermatitis is a parasitic disease that causes an allergic reaction in the skin (swimmer's itch) as a consequence of contact with cercariae of bird schistosomes present in water, mainly of the genus Trichobilharzia Skrjabin et Zakarow, 1920. The main objective of the study was to confirm the presence of the zoonotic disease agent following reports of human infections in recreational water in Slovakia. We identified two species of freshwater snails at Košice Lake, Radix auricularia (Linnaeus, 1758) and Physa acuta (Draparnaud, 1805). Trematode infections were observed only in R. auricularia. Of the 62 snails collected, 11 (17.7%) were infected with 5 different species of larval stages of trematodes. The blood fluke Trichobilharzia franki was found in 2 (3.2%) of the examined snails. The present record provides the first evidence that T. franki from the pulmonate snail R. auricularia represents a source of human cercarial dermatitis in recreational water in Slovakia. Our finding complements the easternmost records of both swimmer's itch and the confirmed occurrence of a bird schistosome in a waterbody in Europe. The present work suggests that the health risks associated with trichobilharziasis need to be further studied by detailed monitoring of the occurrence of the major causative agent of human cercarial dermatitis, T. franki.
Keywords: Trematode Infections; Zoonosis; Slovenská republika; Animals; parazitární onemocnění kůže; Schistosomiasis; Humans; Trematodes; Cercarial dermatitis; dermatitida; Lakes; infekce červy třídy Trematoda; Schistosomatidae; Bird schistosomes; Cercariae; Trichobilharzia; Zoonoses; schistosomóza; Snails; zoonózy; Disease Outbreaks; zvířata; Dermatitis; Slovakia; jezera; epidemický výskyt choroby; lidé; hlemýždi; Skin Diseases, Parasitic